Oxford Research Encyclopedia of Education 2020
DOI: 10.1093/acrefore/9780190264093.013.666
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior in Educational Institutions

Abstract: Organizational citizenship behavior has recently received much interest as it differentiates between actions in which employees are eager to and not to go beyond their prescribed role requirements in diverse organizations. The claim for organizational effectiveness is generally on the increase, seeing as the world is globalizing. In particular, educational systems are shifting toward an era of reorganization, requiring them to toil in a competitive and complex environment. This makes higher education instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, research has shown that OCB among faculty members is associated with improved student learning outcomes, increased student engagement, and overall institutional effectiveness (Adewale & Ghavifekr, 2019; DiPaola & Hoy, 2005; Dipaola & Tschannen-Moran, 2001). Furthermore, students' perceptions of their instructors' OCB have been found to be positively related to their evaluations of teaching effectiveness, course satisfaction, and perceptions of instructorstudent rapport (Ahmadu & Don, 2020;Boyar & Mosley, 2007;Rego et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research has shown that OCB among faculty members is associated with improved student learning outcomes, increased student engagement, and overall institutional effectiveness (Adewale & Ghavifekr, 2019; DiPaola & Hoy, 2005; Dipaola & Tschannen-Moran, 2001). Furthermore, students' perceptions of their instructors' OCB have been found to be positively related to their evaluations of teaching effectiveness, course satisfaction, and perceptions of instructorstudent rapport (Ahmadu & Don, 2020;Boyar & Mosley, 2007;Rego et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such a connection has not been investigated adequately in the domain of teaching. The idea of citizenship behaviour has become germane to educational institutions and their functioning (Ahmadu and Don, 2020). Jimmieson et al (2010) noted that teacher OCBs improve overall effectiveness and performance of school which in turn positively affects student lives.…”
Section: Introductionmentioning
confidence: 99%